THE EFFECT OF THREE COMMERCIAL FEEDS USED IN AQUACULTURE HATCHERIES ON PHYSIOLOGY OF THE PRAWN Macrobrachium amazonicum (DECAPODA, PALAEMONIDAE) - Gerotto, Amanda [UNESP]; Mantoan, Paulo Victor [UNESP]; Gaeta, Henrique Hessel [UNESP]; Augusto, Alessandra [UNESP] (Inst Pesca, 2015)
We investigated the effect of three commercial feeds containing 32%, 35% (control), and 38% of crude protein on the physiology (metabolism, ammonia excretion, energy substrate and hepatosomatic index) of Macrobrachium amazonicum. The energetic content and energy/protein ratio of the feeds were quantified. The physiological aspects did not show differences among the animals fed with the three types of feeds concerning metabolism, ammonia excretion and energy substrate, which was kept as a proteins. However, we observed 120% higher hepatosomatic index in the animals fed with 38% of protein. This feed has also higher energetic value (4,700 +/- 10.6 kcal kg(-1)) and an energy/protein ratio (12.2:1). It is possible that these characteristics of the feed have contributed to higher hepatosomatic index. In this sense, the feed containing 38% of protein seems to be more appropriate because it may promote better storage of reserves in the hepatopancreas, a beneficial condition to reproduction and growth.
Keywords: freshwater prawn; metabolism; excretion; hepatopancreas; energy; protein